Subcompartmentalization and Pseudo‐Division of Model Protocells. Issue 2 (23rd November 2020) - Spustova, Karolina; Köksal, Elif Senem; Ainla, Alar; Gözen, Irep
Abstract: Membrane enclosed intracellular compartments have been exclusively associated with the eukaryotes, represented by the highly compartmentalized last eukaryotic common ancestor. Recent evidence showing the presence of membranous compartments with specific functions in archaea and bacteria makes it conceivable that the last universal common ancestor and its hypothetical precursor, the protocell, may have exhibited compartmentalization. To the authors' knowledge, there are no experimental studies yet that have tested this hypothesis. They report on an autonomous subcompartmentalization mechanism for protocells which results in the transformation of initial subcompartments to daughter protocells. The process is solely determined by the fundamental materials properties and interfacial events, and does not require biological machinery or chemical energy supply. In the light of the authors' findings, it is proposed that similar events may have taken place under early Earth conditions, leading to the development of compartmentalized cells and potentially, primitive division. Abstract : An autonomous subcompartmentalization mechanism is reported for protocells which results in the transformation of initial subcompartments to daughter protocells. The process is solely determined by the fundamental materials properties and interfacial events. Similar events may have taken place under early Earth conditions, leading to the development of compartmentalized cells and potentially, primitive division.